First-Principles Study of Fluorinated Tetrahexcarbon: Stable Configurations, Thermal, Mechanical, and Electronic Properties - Kilic, Mehmet Emin; Lee, Kwang-Ryeol (American Chemical Society, 2020)
Tetrahexcarbon (TH-carbon) was recently predicted to be a stable two-dimensional semiconductor with an intrinsic direct band gap, making it promising for practical applications in optoelectronic devices. In this work, ab initio density functional theory (DFT) calculations were performed in order to study the possibility of manipulating the essential physical and chemical properties of TH-carbon by fluorination, which significantly change the hybridization states of carbon atoms. The phonon spectrum, ab initio molecular dynamics (AIMD) simulations, and elastic constants results revealed that fluorinated derivatives of TH-carbon are dynamically, thermally, and mechanically stable. Depending on the fluorine coverage, we examined the tunability of the electronic band gap and the direct-indirect-direct band gap transitions. We found that the phononic gap in TH-carbon can be controlled by fluorination. A decrease in the specific heat capacity was observed with increasing fluorine coverage, which is useful for nanoscale engineering of heat management. The fluorination is found to reduce the in-plane stiffness and Young's modulus but it increases the ultimate strength. These results suggest fluorination would enable the ability to tailor TH-carbon material for several interesting technological applications.
Keywords: ULTRASOFT PSEUDOPOTENTIALS; REVERSIBLE HYDROGENATION; PENTA-GRAPHENE; CARBON; DYNAMICS; PHASE